Tribological Behavior of Ionic Liquid with Nanoparticles - Thi-Na Ta (MDPI AG, 2021)
This research aims to formulate a new lubricant containing oxide nanoparticles for enhancing anti-wear ability and reducing friction. Different concentrations of copper oxide (CuO) and zinc oxide (ZnO) nanoparticles were separately added to an ionic liquid, methyltrioctylammonium bis(trifluoromethylsulfonyl)imide [N1888] [NTf2], to formulate the tested lubricants. The tribological properties of the lubricants were tested by performing ball-on-disc wear tests on a tribotester (MTM, PCS Instruments). The results show that both the CuO and ZnO nanoparticles can increase the friction reduction ability of the ionic liquid when used as a neat lubricant. The anti-wear characteristic of the ionic liquid is increased by adding ZnO nanoparticles but decreased by adding CuO nanoparticles. The best tribological performance observed for the concentration of 0.2 wt% ZnO, with the wear scar diameter is reduced by 32% compared to the pure ionic liquid. The results of SEM/EDX analysis on the worm morphologies show different lubrication mechanisms of the nanoparticles in the [N1888] [NTf2], which are tribo-sintering for CuO nanoparticles, and third body with pure rolling effect for ZnO nanoparticles.